Screening for Heat Transport by Groundwater in Closed Geothermal Systems. Issue 3 (17th January 2014) - Ferguson, Grant
Abstract Heat transfer due to groundwater flow can significantly affect closed geothermal systems. Here, a screening method is developed, based on Peclet numbers for these systems and Darcy's law. Conduction‐only conditions should not be expected where specific discharges exceed 10−8 m/s. Constraints on hydraulic gradients allow for preliminary screening for advection based on rock or soil types. Identification of materials with very low hydraulic conductivity, such as shale and intact igneous and metamorphic rock, allow for analysis with considering conduction only. Variability in known hydraulic conductivity allows for the possibility of advection in most other rocks and soil types. Further screening relies on refinement of estimates of hydraulic gradients and hydraulic conductivity through site investigations and modeling until the presence or absence of conduction can be confirmed.